Post 9-11 U.S. Muslim Labor Market Outcomes - Faisal Rabby; William M. Rodgers (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Using a difference-in-differences framework and micro data from the Current Population Survey-Merged Outgoing Rotation Group Files (1999 to 2004), this paper estimates the impact that the 9-11 terrorists attacks had on the U.S. labor market outcomes of individuals with nativity profiles similar to the terrorists. We find that shortly after the attacks, the employmentpopulation ratios and hours worked of very young (ages 16 to 25) Muslim men fell. By 2004, most losses had begun to dissipate. The employment-population ratios and hours worked of older Muslim men experienced little deterioration.
Keywords: J15; J61; J71; 330